2019
DOI: 10.14295/oh.v25i2.1727
|View full text |Cite
|
Sign up to set email alerts
|

Seed position and influences on Caesalpinia pulcherrima germination and reserve proteins

Abstract: Caesalpinia pulcherrima has diverse uses in the world, including ornamental and landscape characteristics, but there is a great disparity of germination during the time of seedlings production, being this factor attributed to the position of the seeds in fruits. This study aimed to evaluate some germinative aspects and concentration of reserve proteins in C. pulcherrima seeds in the function of its position in fruits. The work was carried out in greenhouse, in a completely random experimental design, with five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Similar effects to the present study were observed in other crops by Gehling et al (2017) in soybean (Glycine max) and Gehling et al (2014) in wheat (Triticum aestivum), as the authors verified that higher concentrations of A. nodosum seaweed extract improved seed germination. The germination rate and mean germination time are inversely proportional; thus, higher the GSI means lower TMG (Santos et al, 2019); accordantly, seeds treated with 15 mL L -1 biostimulant germinated earlier (5.6 days) and higher speed (1.13). Seeds with high GSI and low TMG values are more resistant to the adverse germination conditions, as they germinate faster and the initial stage of development of seedling production is decreased (Oliveira et al, 2009).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Similar effects to the present study were observed in other crops by Gehling et al (2017) in soybean (Glycine max) and Gehling et al (2014) in wheat (Triticum aestivum), as the authors verified that higher concentrations of A. nodosum seaweed extract improved seed germination. The germination rate and mean germination time are inversely proportional; thus, higher the GSI means lower TMG (Santos et al, 2019); accordantly, seeds treated with 15 mL L -1 biostimulant germinated earlier (5.6 days) and higher speed (1.13). Seeds with high GSI and low TMG values are more resistant to the adverse germination conditions, as they germinate faster and the initial stage of development of seedling production is decreased (Oliveira et al, 2009).…”
Section: Resultsmentioning
confidence: 92%
“…The root length of soybean seedlings was not affected by seaweed extract, which is probably due to the volume of tray limiting root system growth and development (Gehling et al, 2017). The size and volume of the cells in germination tray directly affects root architecture, due to restricted area that limits root growth, which may compromise shoot growth and development (Santos et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The Leguminosae species Caesalpinia pulcherrima (L.)Sw. and Delonix regia (Bojer ex Hook.)Raf. are native from Central America and Madagascar, respectively, but they are widely used as ornamental plants around the world (Singh and Kumar 2014;Santos et al 2019). Their easily extractable galactomannans have been exploited as dietary ber, fruit edible coating, preparation of mucoadhesive microspheres, drug delivery systems and injectable regenerative hydrogels (Cerqueira et al 2009;Tamaki et al 2010;Lima et al 2010;Thombre and Gibe 2013;Buriti et al 2014;Ogunjimi et al 2017;Lima et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to Santos and Castilho (2018) and Maldaner et al (2019), an ideal substrate for ornamental species must present good conditions of aeration, pH, electrical conductivity, water retention capacity, nutritional availability, and density, in order to result in lower expenses and, consequently, increase healthy seedlings sale (Santos et al 2019).…”
Section: Introductionmentioning
confidence: 99%